Religion and Contraceptive use among Sexually Active Adolescent Girls in Kenya - Ondieki Diana Kerubo; Penfold Suzanne (New Horizons in Medicine and Medical Research Vol. 10, 2022)
This study sought to determine whether type of religion is associated with modern contraceptive use among sexually active adolescent girls in Kenya. According to the 2014 Kenya Demographic Health Survey (KDHS), 50 percent of Kenyan women aged 20 to 49 had their first sexual experience by the age of 18. Early sexual start has been linked to negative health consequences such as undesired adolescent pregnancies, sexually transmitted infections (STIs), and cervical cancer. One in every five teenage girls aged 15-19 is either pregnant with their first child or has had a live birth. Secondary analysis of the Kenyan DHS 2014 female dataset was conducted using a cross-sectional study approach. 732 sexually active adolescent girls aged 15 to 19 took part in the study. The current usage of a contemporary contraceptive technique was the primary outcome measure. The researchers ran descriptive, bivariate, and multivariate logistic regression analyses. For all calculations, the sampling probabilities were adjusted. The proportion of sexually active adolescent girls reporting current use of modern contraception was 30.2%. By religious group, 30.7% of Christians and 21.1% of Muslims were currently using modern contraception. In Kenya, the modern contraceptive prevalence rate (CPR) was low among sexually active adolescent girls aged 15 to 19. Adolescents of various religions did not differ in their usage of modern contraceptives.